Daños causados por el Terremoto de Limón: pérdidas y medidas de mitigación - Morales, Luis Diego (2011)
The earthquake affected an area of 8,000 km2 which includes 80% of Costa Rica's and 20% of Panma's territory. The most important losses and damages occurred to the vital lines such as roads, railroads, bridges, ports and water pipes. The roads between Siquirres and Limon and between Limon and Sixaola were the most affected and a total of 309 km was necessary to rebuild or lo rehabilitate. Four bridges collapsed to the south of Limon and another six bridges were highly damaged to the west of Limon. Several type of harms ocurrod along 92 km of railroads due to tectonic uplifting and sea water level decreased, limiting dock 's capacity. Water supply shortage of Limon city spanned for about three months after the earthquake due to severe water pipes damages. All damages considered together amount 188.3 million US$, which is equivalent to 4.21 % of the Gross National Product. During the emergency phase priorities were given to humanitary assistance by plane, a communication network and several brigades i.e. health, lodging, and supplies. In addition, a seismic activity and basin observation plan was established together with docks and canals dredging.